The role of macroeconomic fundamentals in Malaysian post recession growth. - Lee, Chin (Springer, 2013)
This study aims to find out the role of macroeconomic fundamentals in Malaysian post recession growth. The selected macroeconomic variables are exports, imports, price level, money supply, interest rate, exchange rate and government expenditure. The technique of cointegration was employed to assess the long run equilibrium relationships among the variables. Then, this study performs the Granger causality tests based on VECM to establish the short run causality among the variables. The long-run cointegrating relationship shown that an increase in exports, government expenditure or depreciation of exchange rate will promote long-term economic growth while increase in inflation, interest rate and imports will tamper the Malaysian economic growth. The results of short-run Granger-causality indicated that price level and government spending Granger-caused economic growth in the short-run. In conclusion, based on the results of long-run and short run analysis, the fiscal policy is probably the most appropriate tool in promoting economic growth in Malaysia during the post recession period.